An integrative review of research on gambling and domestic and family violence: Fresh perspectives to guide future research - Hing, Nerilee; O’Mullan, Cathy; Mainey, Lydia; Greer, Nancy; Breen, Helen (Frontiers in Psychology, 2022)
This paper presents an integrative review of research on domestic and family violence (DFV), including intimate partner violence (IPV), experienced by victims and perpetrators with a gambling problem. It aims to review, critique, and synthesize research on this topic to generate fresh and alternative perspectives to guide future research. Based on a systematic search of the academic literature and a targeted search of gray literature, the paper summarizes findings from empirical studies pertaining to the prevalence of perpetration and victimization, characteristics of perpetrators and victims, and explanations for this violence. Based on this review, the paper suggests several potential improvements that can be considered in future studies. These include a shift from focusing on situational violence to also include coercive control; greater sensitivity in research design and interpretation to gender differences in experiences of violence; and the need to include economic abuse as a form of DFV/IPV. Adopting a public health lens is also recommended to broaden the research focus from victims and perpetrators to also consider contextual factors. In particular, gambling research should examine the contribution of gambling products, practices, environments, and marketing to DFV/IPV and how this might be ameliorated. While research to date has drawn much needed attention to the risks that gambling presents for DFV/IPV, this review provides some suggestions for future research so that it can provide more nuanced findings to inform policy and practice.